0014 Developing simpatico – simulation for de-escalation, conflict resolution and rapport building. (2nd November 2015) - Campbell, Lloyd; Cross, Sean
Abstract : Background/context: South London and Maudsley NHS Foundation Trust's (SLaM) work in the area of the prevention and management of violence and aggression has revealed a limitation in the usual 'didactic sessions combined with physical skills training' approach to such training. Owing to the need to address learning objectives in the national syllabus 1 and have participants demonstrate competency in prescribed physical techniques, there is not enough time to show suitable stringency in training for de-escalation and negotiation skills – skills vital to avoiding incidents and the need for physical intervention altogether. A course was developed for all front line staff, designed to enhance knowledge, confidence and clinical skills through discussing models of conflict, negotiation/communication skills and/or having a forum to explore alternative strategies for de-escalation. Methodology/description: The one-day course was delivered on four occasions during its pilot phase. It consisted of a mini- workshop on models of conflict and five scenarios, each followed by a structured debrief. Iterative design was implemented whereby feedback from each course contributed to the next. Participants (n = 36) were a variety of health professionals from multiple backgrounds who have regular patient contact in inpatient settings. Scenarios involved negotiating various types of conflict. Debriefs encouraged learners to discuss and reflect on effective strategies/tools for specific conflict types. Results/outcomes (Anticipated): Positive feedback is anticipated along with pre-post measures of knowledge and confidence to show significant increases. It is also predicted that follow-up measures will show drops in incidents over a 12-month period and indicate simulation's utility in communication training. Potential impact: Further research will be conducted on 'Simpatico' as it is implemented on a larger scale, but similar projects have indicated potential for simulation to be a valuable learning tool both to improve de-escalation/negotiation skills and to aid the general development of frontline staff in mental health settings. Reference: http://www.nhsbsa.nhs.uk/Documents/psts_implementing_syllabus.pdf